Catalytic Hydrodeoxygenation of Bio-oil Model Compounds over Pt/HY Catalyst - Lee, Heejin; Kim, Hannah; Yu, Mi Jin; Ko, Chang Hyun; Jeon, Jong-Ki; Jae, Jungho; Park, Sung Hoon; Jung, Sang-Chul; Park, Young-Kwon (NATURE PUBLISHING GROUP, 2016)
The hydrodeoxygenation of a model compound of lignin-derived bio-oil, guaiacol, which can be obtained from the pyrolysis of biomass to bio-oil, has attracted considerable research attention because of its huge potential as a substitute for conventional fuels. In this study, platinum-loaded HY zeolites (Pt/HY) with different Si/Al molar ratios were used as catalysts for the hydrodeoxygenation of guaiacol, anisole, veratrole, and phenol to a range of hydrocarbons, such as cyclohexane. The cyclohexane (major product) yield increased with increasing number of acid sites. To produce bio-oil with the maximum level of cyclohexane and alkylated cyclohexanes, which would be suitable as a substitute for conventional transportation fuels, the Si/Al molar ratio should be optimized to balance the Pt particle-induced hydrogenation with acid site-induced methyl group transfer. The fuel properties of real bio-oil derived from the fast pyrolysis of cork oak was improved using the Pt/HY catalyst.
Keywords: NOBLE-METAL CATALYSTS; NI-BASED CATALYSTS; SUPERCRITICAL ETHANOL; PYROLYSIS OIL; GUAIACOL; BIOMASS; LIGNIN; ANISOLE; DEOXYGENATION; LIQUEFACTION